Critical reading in higher education: A systematic review - Van, L.H. (Elsevier Ltd, 2022)
It is believed that together with critical thinking, critical reading has emerged as a fundamental skill that university graduates are expected to possess in an increasingly modern and digitally connected world (BrÃ¥ten & Braasch, 2017). With the advancement of technology, young adults have been increasingly submerged in a sea of information available at their fingertips. Hence, they must learn how to select, analyze, evaluate, and assess the information they encounter in their academic or professional lives (Siemens, 2004). However, it is observed that critical reading skills in higher education seem to be neglected in the research field compared to an interest in critical thinking studies. This study systematically evaluates 75 papers published between 2001 and 2021 and indexed in the Web of Science and Education Resources Information Center (ERIC) databases. The findings indicate that scholars in Turkey and the United States place a higher premium on critical research than researchers in other parts of the world. Most papers focus on investigating feasible approaches to develop critical reading skills amongst undergraduates and proposing critical reading pedagogy in higher education institutions. However, there has been a deficiency in research of critical reading in STEM education, especially in the Asian tertiary context. This study highlights the significance of conducting additional in-depth research into the effects of integrating critical reading classrooms and teaching-and-learning activities into STEM education, as well as the impact of using science topics with the goal of cultivating this crucial skill for young people's academic and professional development in the era of the digital revolution. Moreover, research on a conceptual framework to develop critical reading abilities amongst Asian undergraduates could be considered as a potential topic for novice researchers. Â© 2022 Elsevier Ltd